Metadata formats and the new markup language from library field - Salgáné Medveczki, Marianna (Teaching Mathematics and Computer Science, 2005)
Using new communication technologies libraries must face continuously new questions, possibilities and expectations. This study discusses some library-related aspects of our electronic era and how computer-related data formats affect bibliographic dataprocessing to give a survey of the most important results. Altough library systems have been supporting the creation and maintenance of MARC records for decades, the need to create other forms of metadata is relatively new. In higher education it is important that students get acquainted with these new aspects of bibliographic description and bibliographic dataprocessing. In our department I launched the BDML development project in order to standardize bibliographic description (based on Hungarian standard 3424/1) with the help of XML. The development aims at the creation of a set of standards that provides information about the structure of bibliographic description in XML form. In the second part of the paper I give a brief presentation and summary of BDML.